Sistem Pembacaan Nada Trumpet dengan Metode Fast Fourier Transform (FFT) Berbasis Embedded System - A. Baihaqi Mubarok; Dahnial Syauqy; Issa Arwani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Marching bands are an art group that half of the composition is brass players. However, in Indonesia some trumpet players in the marching band did not understand the C D E F A B C tone theory, including the method for tuning tools. In this study a tuning system for trumpet with FFT (fast fourier transform) algorithm was developed. The system developed uses a USB microphone as a sensor, data processing is done with Raspberry Pi 3. FFT processing uses the Numpy library, in which there are several subprocesses, from taking signal samples to windowing. After the window is obtained, the FFT can be calculated, and then the results of the FFT will be converted into a frequency domain and then converted to pronunciation notation (do, re, mi, fa, sol, la, si, do). The output of this process is the frequency and notation displayed on the 16 x 2 LCD. The test results on the sensor can capture various sounds, and the test results on the system can capture chromatic tones between octaves 3 to 4, with an average the difference in frequency is 1.85 Hz. In testing the computation time, the average results were 0.28 seconds.